An English for Research Publication Purposes Course: Gains, Challenges, and Perceptions - Giraldo, Frank (GIST – Education and Learning Research Journal, 2019)
Academic writing for scholars wanting to publish in English has gained considerable research attention in academic writing circles. This article reports the findings of a case study on the gains, challenges, and perceptions about writing in English that a group of scholars had while taking an academic writing course. Two questionnaires, an in-depth interview, and a teacher-researcher’s journal were used for data collection. The findings emphasize gains emerging from genre-based pedagogy as a holistic approach to academic writing and usefulness of teaching strategies for writing. The study reports time, discipline, and language proficiency as challenges to overcome. Finally, the participants report differing views towards peer feedback and a predominantly positive perception of English as the language for scientific writing.